Deformation behavior of polypropylene fiber reinforced concrete subject to compressive fatigue loading: Averaged ε-n curve and probabilistic ultimate fatigue strain model - Cui, Kai; Xu, Lihua; Chi, Yin (Composite structures, 2025)
Polypropylene fiberis recognized as a lightweight and corrosion-resistantpolymeric material. Incorporating polypropylene fibers into the matrix substantially enhances the crack resistance and refines the pore size distribution of concrete, thereby prolonging its service life. In this work, we systematically examined the compressive fatigue deformation behavior of polypropylene fiber reinforced concrete (PFRC). A total of 18 groups of concrete samples subjected to various stress levels were tested, with an emphasis on unveiling the effect of polypropylene fiber volume fraction and aspect ratio on the fatigue strain growth rate and ultimate fatigue strain of PFRC. The results have shown that the presence of polypropylene fibers substantially mitigates the fatigue strain growth rate and improves the fatigue deformation capacity. Based on a proposed method for generating an averaged ε-n curve of six replicate specimens, it is observed that as the volume fraction increases from 0 to 0.2%, the fatigue strain growth rate of concrete exhibits a trend of initial decrease followed by a subsequent increase, while an increase in the aspect ratio from 167 to 396 leads to an acceleration in the fatigue strain growth rate. Furthermore, the ultimate fatigue strain of concrete exhibits a positive correlation with an increase in the volume fraction and aspect ratio. In comparison to plain concrete, the ultimate fatigue strain of PFRC can be increased by up to 15.9%. Finally, based on the static peak strain distribution of plain concrete, a probabilistic model was put forward to describe the probability distribution of the ultimate fatigue strain of PFRC under various stress levels. This model yields accurate predictions that are in close alignment with a broad spectrum of test results, demonstrating its wide applicability in estimating the ultimate fatigue strain of PFRC.